2017
DOI: 10.5897/ajb2017.15969
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and genetic variability of partial coat protein gene of Sweet potato leaf curl virus (SPLCV) in Kenya

Abstract: A survey was conducted to determine the occurrence of sweet potato leaf curl virus (SPLCV) infecting sweet potato in Kenya. Vine cuttings of sweet potato were collected in 2011 from fields in Central, Western and Coastal regions of the country. The cuttings were grown in an insect-proof screen-house and scion grafted to Ipomoea setosa indicator plants. DNA was extracted from leaf samples of graftinoculated I. serosa and tested for the presence of SPLCV by polymerase chain reaction (PCR) using degenerate and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Miano et al(2006) reported the occurrence of sweepoviruses in an agricultural field station in Kenya. Countrywide surveys conducted in 2011 (Maina, 2014; Maina et al 2017) and (Wanjala, 2016/2017 - unpublished data ) confirmed sweepoviruses to be present in the major sweetpotato growing regions of the country. The presence of sweepovirus inoculum in major sweetpotato producing areas in Kenya and the continuing expansion of the vector - Bemisia tabaci (Simmons et al 2008) might have contributed to its broad geographic distribution in Kenya.…”
Section: Introductionmentioning
confidence: 96%
“…Miano et al(2006) reported the occurrence of sweepoviruses in an agricultural field station in Kenya. Countrywide surveys conducted in 2011 (Maina, 2014; Maina et al 2017) and (Wanjala, 2016/2017 - unpublished data ) confirmed sweepoviruses to be present in the major sweetpotato growing regions of the country. The presence of sweepovirus inoculum in major sweetpotato producing areas in Kenya and the continuing expansion of the vector - Bemisia tabaci (Simmons et al 2008) might have contributed to its broad geographic distribution in Kenya.…”
Section: Introductionmentioning
confidence: 96%